2004
DOI: 10.1021/je034209e
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Molar Volumes and Viscosities of Some Amino Acids in Aqueous Sodium Acetate Solutions at 298.15 K

Abstract: Apparent molar volumes, V 2 , φ , and viscosities, η, of glycine, dl-α-alanine, dl-α-amino-n-butyric acid, l-leucine, and l-phenylalanine in water and in (0.5, 1.0, 2.0, 4.0, and 5.5) mol·kg-1 aqueous sodium acetate solutions have been determined at 298.15 K from densities and flow time measurements, respectively. The standard partial molar volumes, V ∞ 2, obtained from V 2 , φ , have been used to calculate the corresponding volume of transfer at infinite dilution, Δt V ∞ , from water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
114
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(139 citation statements)
references
References 24 publications
25
114
0
Order By: Relevance
“…Thermodynamic properties of amino acids in aqueous electrolyte solutions provide valuable information about solute-solvent and solute-solute interactions. The effect of electrolytic solutions on amino acids has already been revealed by many works [46][47][48][49][50]. A better insight into the effect of electrostatic and hydrophobic interactions on the stability of proteins can be obtained from salts such as tetramethylhalides which are known to influence macromolecular conformations by weakening attraction or repulsion of inter and intra charge-charge interactions and by affecting hydrophobic interactions through the side chain of the alkyl groups.…”
Section: Surfactant-amino Acid Interactionsmentioning
confidence: 99%
“…Thermodynamic properties of amino acids in aqueous electrolyte solutions provide valuable information about solute-solvent and solute-solute interactions. The effect of electrolytic solutions on amino acids has already been revealed by many works [46][47][48][49][50]. A better insight into the effect of electrostatic and hydrophobic interactions on the stability of proteins can be obtained from salts such as tetramethylhalides which are known to influence macromolecular conformations by weakening attraction or repulsion of inter and intra charge-charge interactions and by affecting hydrophobic interactions through the side chain of the alkyl groups.…”
Section: Surfactant-amino Acid Interactionsmentioning
confidence: 99%
“…These may result from the interaction of ions with the glutamine dipeptide. The interaction of the ions of sodium carboxylate with the glutamine dipeptide increases in the order NaC 2 < NaC 4 < NaC 6 . The stronger the interactions of ions of NaC 6 with dipeptide are, the larger the radii of solvated ions are, and then the mobility of ions decreases.…”
Section: Limiting Molar Conductivity and Walden Products Of Nacmentioning
confidence: 99%
“…Sodium carboxylate containing the large-size anions is known to influence the dissociation of proteins in solutions [4]. The effect of some alkali metal and alkaline earth metal carboxylates on the physico-chemical properties of amino acids has been studied by some workers [5][6][7][8][9] and our group [10][11][12][13][14] in order to understand the fine details of the interactions of the protein with carboxylate salts. In recent years, we have carried out the investigations on thermodynamic properties of some small peptides in aqueous sodium carboxylate solutions [15][16][17][18] because small peptides contain more complex structure and more components of proteins than amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Viscosity studies of some amino acids and peptides have been reported for alkali chlorides [3], KSCN [4,5], NH 4 Cl [6], urea [7], sodium butyrate [8], sodium acetate [9,10], tetra-n-alkylammonium bromide [11,12], caffeine [13], sodium caproate [14], MgCl 2 [15], NaC 6 [16], CaCl 2 [17], magnesium acetate [18], tetramethyl ammonium iodide [19], Cu II nitrate and Ni II chloride [20], surfactant [21], methanol [22], d-glucose [23], potassium citrate salt solutions [24], and KCl and KNO 3 solutions [25]. Kumar et al [11,26,27] have reported the effect of NaBr, KCl, KBr, MgCl 2 , and Na 2 SO 4 on viscosity values of some amino acids and glycylglycine.…”
Section: Introductionmentioning
confidence: 99%